Peran Public Speaking dalam Kepemimpinan dan Teknologi Informasi dengan Neuro Linguistic Programming - Sawali Wahyu (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The Leadership Training Program organized by the BEM of the Faculty of Computer Science, Esa Unggul University, is carried out with the motto "Becoming a leader with neuro-linguistic programming". This activity is one way to increase the knowledge of the Faculty of Computer Science academics about public speaking. The leadership training program is a routine activity carried out by BEM of the Faculty of Computer Science every year with the aim of instilling a spirit of organizational framework in each participant. In this activity material is given about public speaking, so that students can speak in public in everyday life, be it information transmission, motivation or presentation. Students can study neuro-linguistic programming (NLP) technology for approaches to communication and self-development. For this community service activity, students also get case studies that allow them to independently solve problems in public speaking. This can help students explore themselves to convey or present something that is useful for public speaking skills.